2020
DOI: 10.1016/j.therap.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Synthèse des recommandations de l’International Association of Therapeutic Drug Monitoring and Clinical Toxicology (IATDMCT) sur le suivi thérapeutique pharmacologique du tacrolimus

Abstract: Synthèse des recommandations de l'International Association of Therapeutic Drug Monitoring and Clinical Toxicology (IATDMCT) sur le suivi thérapeutique pharmacologique du tacrolimus* Summary of the recommendations of the International Association of Therapeutic Drug Monitoring and Clinical Toxicology (IATDMCT) on the therapeutic drug monitoring of tacrolimusRecommandations IATDMCT sur le STP du tacrolimus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Therefore, instead of using C 0 alone to guide tacrolimus therapy, it is now recommended to use both the C 0 and AUC 0–12 for recipient management, at least once within the early period after transplantation and at another time within the stable phase. 38 …”
Section: When Is Tdm Most Beneficial?mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, instead of using C 0 alone to guide tacrolimus therapy, it is now recommended to use both the C 0 and AUC 0–12 for recipient management, at least once within the early period after transplantation and at another time within the stable phase. 38 …”
Section: When Is Tdm Most Beneficial?mentioning
confidence: 99%
“…For tacrolimus, another widely used calcineurin inhibitor (i.e., a drug that inhibits the T‐cells of the immune system), it was found that patients with identical C 0 may have very different AUC 0–12h , which explains differences in treatment efficacy. Therefore, instead of using C 0 alone to guide tacrolimus therapy, it is now recommended to use both the C 0 and AUC 0–12 for recipient management, at least once within the early period after transplantation and at another time within the stable phase 38 …”
Section: When Is Tdm Most Beneficial?mentioning
confidence: 99%